Educational intervention in breast cancer screening uptake, knowledge and beliefs among Yemeni female school teachers in the Klang Valley, Malaysia - Noman, Sarah Noman Abdulrahman (2020)
Breast cancer (BC) is the most frequently diagnosed cancer among women worldwide. The role of teachers in educating and communicating with students plays an essential role in health education and in the promotion of healthy behaviour such as BCS. This study aims to develop, implement, and evaluate the effectiveness of an educational intervention on BCS using the Health Belief Model (HBM). The highlighted outcomes of the sample include their BCS uptake, knowledge, and beliefs. A cluster-randomised controlled trial was conducted among 180 female Yemeni teachers in twelve schools in the Klang Valley, Malaysia with the schools as the unit of randomisation (clusters). A random assignment of the target schools was made using the block randomisation technique to either include them within the intervention or the control group. The intervention group were offered a 90-minute one-day BCS educational intervention session, while the same offer was made to the control group at the end of the study. The data were collected at baseline, 1-month post intervention followed by 3 and 6-months follow-up assessments using reliable and valid Arabic questionnaires. Data analysis was performed using the SPSS software 22.0. Generalized Estimating Equations (GEE) with a confidence interval of 95% and P-value less than 0.05 were conducted to assess the differences between group and within group effects, and the interaction effect over time. There were no statistically significant differences between the two groups regarding the respondents' characteristics and the outcome variables at baseline. Generally, the groups demonstrated an overall significant higher changes in breast self-examination (BSE), and in clinical breast examination (CBE) post intervention for the intervention group than the control group with adjusted odds ratio (AOR) of 17.51 (CI: 8.22-37.29) and 2.75 (CI: 1.42-5.32) respectively. The AOR of BSE performance within the intervention group was increased over the six months from 11.01 (CI: 5.05-24.04) to 18.55 (CI: 8.83- 38.99). Similarly, the AOR of CBE uptake within the intervention group was increased from 1.60 (CI: 1.02-2.52) to 2.27 (CI: 1.44-3.58). For secondary outcomes, the between and within groups analysis showed an overall significant increase in the mean knowledge scores for the intervention group than the control group at (P<0.001). The results for between groups indicated overall significant differences in the mean beliefs scores for benefits of BSE (P<0.001), barriers of BSE (P<0.001), confidence on the ability to do BSE (P=0.014), health motivation (P<0.001), benefits of MMG (P=0.025), and benefits of CBE (P<0.001). Furthermore, within group analysis over the six months found the mean health beliefs scores in the intervention group increased significantly than the control group for benefits of BSE (23.20 to 26.22, P<0.001), confidence in the ability to perform BSE (30.34 to 35.30, P<0.001), benefits of CBE (15.73 to 16.76, P=0.031), and benefits of MMG (21.94 to 23.99, P=0.017). Besides, there has been a significant decrease in the barriers towards BSE (12.81 to 11.00, P=0.002). These results show the effectiveness of educational intervention based on the HBM in improving BSE and CBE uptake, knowledge, and in reducing barriers.